FY2018 Gulf Cooperation Council Countries Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The Country Opinion Survey in Bahrain assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Bahrain perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Bahrain on 1) their views regarding the general environment in Bahrain; 2) their overall attitudes toward the WBG in Bahrain; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Bahrain; and 4) their perceptions of the WBG’s future role in Bahrain.